A1.31 Monoclonal antibodies from CD19+ synovial B cells of RA patients with tertiary lymphoid structures display a strong immunoreactivity towards citrullinated histones from neutrophils NETs. (31st January 2014) - Corsiero, Elisa; Carlotti, Emanuela; Wardemann, Hedda; Robinson, William; Migliorini, Paola; Pratesi, Federico; Pitzalis, Costantino; Bombardieri, Michele
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is characterised by breach of self-tolerance towards citrullinated proteins. Moreover, RA patients are characterised by increased neutrophils in their synovial fluid, in particular at early stage of the disease. Recent evidence suggests a critical role of neutrophils in sustaining the inflammatory response in the RA joint. Around 40% of patients display synovial tertiary lymphoid structures (TLS) with functional B cell follicles supporting a germinal-centre response and local autoantibody production. However, the nature of the main (auto)antigenic reactivity of synovial B cells is unknown. Here we characterised the autoreactive B cell response of lesional B cells isolated from TLS + RA synovium. Materials and Methods: Single CD19 + B cells were FACS sorted from synovial cell suspension of 4 TLS + RA patients. RNA was used to amplify Ig VH and VL genes and PCR products were cloned and expressed as recombinant monoclonal antibodies displaying identical specificity of the original B cells. Recombinant antibodies were then tested 1) to determine the frequency of polyreactive clones and 2) to define their immunoreactivity towards native and citrullinated antigens using a synovial antigen microarray platform. Results: We obtained 139 individual VH sequences of which 33% were IgM, 40% IgG, 27% IgA and 175 VL sequences and we generated a total of 66 complete (H + L chains) recombinant monoclonal antibodies. Analysis of the VH gene somatic mutation rate showed evidence of antigen selection and intra-synovial clonal diversification. No skewed distribution of the VH and VL gene usage was observed. Around 30% of synovial monoclonal antibodies were reactive towards citrullinated histones in the antigen microarray, in particular citH2A and citH2B. This reactivity was confirmed by citH2A and citH2B ELISA. Moreover, when the synovial monoclonal antibodies were tested on neutrophil extracellular traps (NETs), which contained citrullinated histones, reactivity towards NETs proteins but not neutrophil nuclear antigens was observed. Conclusions: Here we provided novel evidence that highly mutated, locally differentiated B cells within RA synovial germinal centre-like structures display a strong immunoreactive bias towards citrullinated histones which likely derived from neutrophil NETs that continuously form in the RA synovial fluid. This suggests that citrullinated histones are the main antigens driving in situ B cell activation and differentiation sustaining the humoral autoimmune response within the RA joints.